Análisis de la relación entre el déficit presupuestario y la provisión de efectivo - Hussein, Burhan Othman (Opción, 2019)
This investigation is carried out with the objective to reassess this notion in the context of under developed economy. A long run relationship between inflation, money supply and budget deficit is investigated using time series data consisting time period of 1975 to 2017 as a method. As a result, the evidence does not support the hypothesis that money supply is associated with budget deficit in long run. However, inflation and money supply has long run one way relationship in Iraq. Therefore, this research conclude that budget deficit constrains does not bring changes in monetary policy in Iraq